The degree of teaching competencies exercised by the faculty members in light of the overall quality management criteria from the view of the students of the Faculty of Education at Al-Baha University - Mohammad Aboud AL- harahsheh; Yasien Abdel Wahhab Yasien Ahmad (University of Science and Technology, Yemen, 2013)
Abstract The study aimed at recognizing the degree of teaching competencies exercised by the faculty members in light of the overall quality management criteria from the view of the students of the Faculty of Education at Al-Baha University, as well as the impact of social gender and educational program on the degree of practicing teaching competencies in light of the overall quality management criteria. The sample of the study consists of 375 students, who received a questionnaire composed of 72 paragraphs, distributed into four prime areas, namely; (planning, implementation, evaluation and communication). The study concluded to the following results: the degree of practicing teaching competencies by the faculty members is medium. The study showed that there is a variation of statistical significance in the degree of practicing teaching competencies by the faculty members in light of the overall quality management criteria on the field of evaluation, communication and the total due to gender variables which came in favor of male. Meanwhile, the results of the study showed that there are differences of statistical significance in the degree of teaching competencies practices exercised by the faculty members in light of the overall quality management criteria on all aspects of the studied areas and the instrument as a whole due to the level of the program and in favor of the Master and Diploma programs. Key words:  Faculty Members, Teaching Competencies Overall Quality Management Criteria, and Al-Baha University.